Personality Psychology in the Workplace. 2001
DOI: 10.1037/10434-002
|View full text |Cite
|
Sign up to set email alerts
|

Citizenship performance: Its nature, antecedents, and motives.

Abstract: his chapter introduces the topic of contextual or citizenship performance and reviews research on this element of performance. In particular, it (a) T describes an initial model of citizenship performance and how this performance domain is different from task performance; (b) discusses the origins of the construct (i.e., precursors to the citizenship performance concept); (c) reviews three research areas that represent attempts to learn more about citizenship performance; (d) describes research on motives f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 36 publications
1
30
1
2
Order By: Relevance
“…This perception agrees with the importance of political skills in adapting positively to the workplace (Ferris et al, 2000; Perrewé et al, 2000). The quality of perseverance, as well as the ability to remain well-balanced in a dispute are considered both within the context of political skills and as a personality traits favouring OCBs (Borman & Penner, 2001). In addition, all three elements which emerged in this category confirmed the most recent views on resilience as a promoter of well-being in the workplace (Cooper, 2010; Ferguson, 2009; Magrin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This perception agrees with the importance of political skills in adapting positively to the workplace (Ferris et al, 2000; Perrewé et al, 2000). The quality of perseverance, as well as the ability to remain well-balanced in a dispute are considered both within the context of political skills and as a personality traits favouring OCBs (Borman & Penner, 2001). In addition, all three elements which emerged in this category confirmed the most recent views on resilience as a promoter of well-being in the workplace (Cooper, 2010; Ferguson, 2009; Magrin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As the attribution theory suggests, when people observe certain behaviors, people tend to make dispositional attribution on behaviors that are under the control of the actors [17,18]. In recent years, the attribution perspective has been widely used in the studies on organizational behavior [19][20][21]. The extant research has shown that performance appraisals are significantly influenced by the supervisor's attribution of an employee's motives behind certain behaviors [22,23], implying that when employees make suggestions and/or present new ideas, their motives will be perceived and attributed by supervisors, thereby influencing their performance appraisals.…”
Section: Introductionmentioning
confidence: 99%
“…Competitive and high-performance organizations, such as some universities, expect their workforce to perform above and beyond their formal duties in return for more tangible and symbolic rewards and support, including appreciation and respect. Another dimension of these expectations for extra behavioral performance has recently been researched around the theme of Organizational Citizenship Behavior (OCB) (Borman and Penner, 2001;Organ and Ryan, 1995;Schappe, 1998). In a paper devoted to the causes of OCB, Rioux and Penner (2001) wrote: "Much of the current research on the causes of OCB either implicitly or explicitly assumes that engaging in such behavior is a reaction or a response to an individual's perceptions of his or her job and the organization for which he or she works" (p. 1306).…”
Section: Introductionmentioning
confidence: 99%